PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) TERHADAP HASIL BELAJAR SISWA PADA MATERI LISTRIK DINAMIS DI KELAS X SEMESTER II SMA NEGERI 12 MEDAN T.P. 2015/2016 - Siagian, Hana Daforosa R; Hutahaean, Juniar (JURNAL IKATAN ALUMNI FISIKA, 2016)
This research is purposed to determine the effect of guided inquiry  model to student learning outcomes   in subject dynamic electricity  in the second half of class X SMAN 12 Medan in academic year 2015/2016. The population is 9 classes and sampling by cluster random sampling. The samples consist of treatment class and control class that were randomly selectedis class X-2 (38 students) as an experimental class and a class X-4 (36 students) as a control class. The instrument used in this study there are two, the first test of learning outcomes in the form of multiple choice with option 5 of 15 questions that have been declared valid by the experts, the second is the observation sheet student learning activities. The research showed the average value of pretest and posttest for the experimental class was 42,46 and 77,02, while the average value for the pretest and posttest control group was 43,89 and 68,15. The  observation of learning activities of students from the first meeting to the third meeting, student learning activities for use guided inquiry model increases, in the first meeting is 57,64  (active enough), meeting II is 71,43  (active) and at meetings III is 82,21 (active). Based on test results obtained by the hypothesis that there is significant effect of guided inquiry model to student learning outcomes in subject dynamic electricity in the second half of class X SMAN 12 Medan in academic year 2015/2016.